Song variations in the White-chested Babbler Trichastoma rostratum - Stephen V Nash; Anne D Nash (KUKILA, 1987)
For few species of birds are the full range of songs and calls known, and in Indonesia little has been published concerning individual song Motives and full repertoires of forest birds, even. though these may differ from published accounts based on mainland Asian individuals (or races). Field identification of Indonesian birds based on vocalizations described in current field guides may for this reason be difficult or even impossible. In this note variations in the full adult song of the male White-chested Babbler Trichastoma rostratum are described, as well as the call of the female bird. Tracings of the original sonograms (audio-spectograms) derived from tape-recorded songs are included to illustrate the descriptions. The tape-recordings were made between 30 April and 16 September, 1985, in both riverine forest and peatswamp forest habitats in the Padang-Sugihan wildlife Reserve, south Sumatra province. The recordings were examined on a Unigon 4500 Uniscan Spectrum Analyzer, and the sonograms were made on a Kay Digital Sono-Graph 7800 set to a wide (300 KHz) band range.